3D GIS for Advanced Building Management - Siti Nurbaidzuri, Reli @ Raily; Sharifah Mazenah, Wan Yusuf; Nurafiza, Aman (Springer Cham, 2025)
Traditionally, building information, particularly in strata title management, has been organized using building plans and extensive data filing systems. While these plans are easily understood by professionals in surveying and architecture, 3D visualization provides a more effective way to convey information to a broader audience. Developing 3D models for stratified property units enhances building information management by integrating these models with corresponding databases, thereby raising the standards of current management practices. Tools like Google SketchUp for 3D modeling and ArcGIS integration play a crucial role in this process. These tools simplify the visualization and understanding of various strata types by offering realistic representations of structures. Previously, data management was a conventional process that required significant physical storage space and resulted in time-consuming data retrieval. Integrating 3D models within a GIS framework revolutionizes this process, streamlining building management and significantly improving efficiency. Additionally, 3D GIS supports better decision-making and planning by providing advanced spatial analysis and visualization capabilities. This integration enhances collaboration among stakeholders, leading to improved communication and a deeper understanding of complex building data.